The role of paralinguistic digital affordances (PDAs) in online mental health communities (OMHCs) in Saudi Arabia - Sara Alrashed; Peter A. Bath; Kushwanth Koya (Information Research: An International Electronic Journal)
Introduction. Depression is a major contributor to disability and will be a leading cause of global disease burden by 2030. There is a high depression rate in Saudi Arabia. Online Mental health communities (OMHCs) are important for people with mental health conditions who are concerned about the stigma associated with these conditions. Paralinguistic digital affordances (PDAs) are a useful social affordance enabled by social media. This study aimed to understand the role of using PDAs in Saudi OMHCs.